Upfront Chemohormonal Therapy for Prostate Cancer: Neutropenia and G-CSF Use. - Buti, Sebastiano; Bersanelli, Melissa (Acta Biomedica Atenei Parmensis, 2016)
After the publication of the results of CHAARTED trial, we discuss an issue of clinical interest about toxicity of this treatment and its prophylactic management. The low rates of neutropenia reported in CHAARTED trial population, compared to those of similar previous studies, need further clarifications about the use of G-CSF, not described by the authors, in order to reproduce this hematological tolerability also in everyday clinical practice. We highlighted the importance of toxicity management and prevention in order to better apply the results of this promising trial in real life patient care.